Impact of Gene Repression on Biofilm Formation of Vibrio cholerae - Pombo, Joao P.; Ebenberger, Stephan P.; Müller, Anna M.; Wolinski, Heimo; Schild, Stefan (Frontiers in Microbiology, 2022)
Vibrio cholerae, the etiological agent of cholera, is a facultative intestinal pathogen which can also survive in aquatic ecosystems in the form of biofilms, surface-associated microbial aggregates embedded in an extracellular matrix, which protects them from predators and hostile environmental factors. Biofilm-derived bacteria and biofilm aggregates are considered a likely source for cholera infections, underscoring the importance of V. cholerae biofilm research not just to better understand bacterial ecology, but also cholera pathogenesis in the human host. While several studies focused on factors induced during biofilm formation, genes repressed during this persistence stage have been fairly neglected. In order to complement these previous studies, we used a single cell-based transcriptional reporter system named TetR-controlled recombination-based in‐biofilm expression technology (TRIBET) and identified 192 genes to be specifically repressed by V. cholerae during biofilm formation. Predicted functions of in-biofilm repressed (ibr) genes range from metabolism, regulation, surface association, transmembrane transport as well as motility and chemotaxis. Constitutive (over)-expression of these genes affected static and dynamic biofilm formation of V. cholerae at different stages. Notably, timed expression of one candidate in mature biofilms induced their rapid dispersal. Thus, genes repressed during biofilm formation are not only dispensable for this persistence stage, but their presence can interfere with ordered biofilm development. This work thus contributes new insights into gene silencing during biofilm formation of V. cholerae.